Role of hybrid arch debranching in the treatment of newly diagnosed aortic arch malperfusion after repair of acute type A aortic dissection - Gasparovic, Ivo (Proc (Bayl Univ Med Cent), 2019)
We present the case of a 41-year-old man who underwent repair of an acute DeBakey type A aortic dissection with a Bentall-De Bono operation and presented with an early aortic arch malperfusion. The malperfusion was successfully treated with a hybrid arch debranching procedure. In this setting, the hybrid arch debranching procedure offers a safe alternative for repair.